Munronoid I Ameliorates DSS-Induced Mouse Colitis by Inhibiting NLRP3 Inflammasome Activation and Pyroptosis Via Modulation of NLRP3 - Ma, Xingyu; Di, Qianqian; Li, Xiaoli; Zhao, Xibao; Zhang, Ruihan; Xiao, Yue; Li, Xunwei; Wu, Han; Tang, Haimei; Quan, Jiazheng; Wu, Zherui; Xiao, Weilie; et al. (Frontiers in Immunology, 2022)
Inflammatory bowel diseases (IBDs) are increasingly common diseases and characterized by chronic and relapsing inflammation of the gastrointestinal tract. NLRP3 might be a crucial regulator of homeostatic balance of intestine, but its upregulation leads to pyroptosis. Munronoid I is extracted and purified from Munronia sinica, which has shown anti-inflammatory effect, but the efficacy of Munronoid I in IBD remains unproven. In this study, we attempted to determine the effect of Munronoid I on NLRP3 to regulate the inflammasome activation and pyroptosis in IBD. Our data demonstrated Munronoid I treatment attenuated DSS-induced the body weight loss, pathological injury of colon, the production of IL-1β and IL-18 and the expression of pyroptosis associated proteins in colon tissue in mice. Moreover, Munronoid I inhibited LPS/ATP-induced pyroptosis in mouse peritoneal macrophages, MODE-K cells and colonic epithelial cells, and decreased the release of inflammatory cytokines IL-1β and IL-18 in mouse peritoneal macrophages. Mechanically, Munronoid I could suppress the NLRP3 inflammasome activation and pyroptosis by promoting the K48-linked ubiquitination and NLRP3 degradation. It is suggested that Munronoid I might be a potential therapeutic candidate for IBD.